Functional upgrading, relational capability and export performance of vietnamese wood furniture producers - Pham Thi Song Hanh (Copenhagen Business School (CBS), 2008)
Departing from my interest in finding key factors determining a developing country firms' export success, this research explores two fascinating topics: one is the debate on whether a developing country's producers should become involved in marketing functions where a developed country's firms already hold a strong position, and the other is the very limited attention given in the export literature to the role of relational capability in a firm's export business....
hdl:10398/7742
Keywords: 650; møbeleksport; møbler; vietnam; eksport; brancheanalyser